Principles of marketing - Kinnear, Thomas C.; Bernhardt, Kenneth L. (Illinois : Scott, Foresman, 1986)
It is organized around the theme of the marketing concepts, which emphasizes that the basic function of marketing is to identify and satisfy consumer needs.
Part 1. Marketing and the environment -- Part 2. The marketplace -- Part 3. Product -- Part 4. Distribution -- Par 5. Promotion -- Part 6. Pricing -- Part 7. Marketing applications: situations, trends and issues.
Includes bibliographical references and index.
Keywords: MARKETING